STRATEGI PEMBANGUNAN PEMERINTAH KAMPUNG DAYUN DALAM MENINGKATKAN STATUS DESA MANDIRI PADA TAHUN 2018 - Nadia Marsanda; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Pemba The development carried out by the Government of Indonesia is a mandate from Law Number 6 of 2014 concerning Villages, in which the Village Government has the authority to regulate and administer village government affairs. The Village Government is given the widest possible authority to administer governance, implement development and empower village communities based on community initiatives, origin rights and village customs. Kampung Dayun is the only Independent Village in Dayun District in 2018, among other villages, on average it is still in a developing status and is able to improve its village status quickly. The government of Kampung Dayun has also optimized its strategy to increase existing development in Kampung Dayun. In achieving the research objectives, researchers used the theory from Rahardjo Adisasmita in 2013 regarding village development strategies. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then the research location is in Dayun Village, Dayun District, Siak Regency, Riau. This study found that the strategy adopted by the Kampung Dayun Government was to fulfill the Village Development Index indicator to improve village status. The development strategies include growth strategies, welfare strategies, strategies that are responsive to community needs and integrated or comprehensive strategies. Among these strategies, the authors conclude that the growth strategy or The Growth Strategy is the most dominant and influential in society. With this strategy, the government of Kampung Dayun increases the income of the village community by conducting basic training, diversity in the productivity of the agricultural sector and the availability of a permanent market and access to credit. With the existence of a strategy that can complement the needs of the community, it forms a good enough economic rotation so that the people of Kampung Dayun have good independence in life. The process of collaboration between actors is also a factor influencing the development of the Kampung Dayun Government in increasing the status of an independent village. Good collaboration between government, non-government actors and village communities. Keywords: Strategy, Development, Independent Village